Dermatitis and its Homeopathic Approach in Different Clinical Repertories (Advancements in Homeopathic Research, 2022)
Dermatitis is most common skin problem all over the  world. In the word “dermatitis,” “derm” means “skin”  and “itis” means “inflammation.” Dermatitis literally  means inflammation of the skin. It is a specific type of  allergic cutaneous manifestation of antigen antibody  reaction. Dermatitis causes no serious harm to your  body. It is not a contagious disease. Homeopathy is  very useful in cases of dermatitis so we should know  its clinical presentation and representation of the  disease in different clinical repertories.
Keywords: Homeopathy; Dermatitis; Clinical repertories; Clarke repertory; Boericke Repertory; Phatak Repertory